Influence of special life circumstances on the risk of injury in alpine skiing a study of athletes on the german ski association's development-team - Goll, M.; Thallmair, L.; Huber, A.; Waibel, K.; Spitzenpfeil, P. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Alpine skiing`s high injury rates require new approaches to mitigate the risk of injury (1). For alpine skiing development athletes there is a lack of research regarding the sport speficic risk factors (2) in both, internal and external factors (3, 1). The basis for appropriate measures consist of new insights into further internal and external risk factors and injury mechanisms (3). Therefore, the research question of this study was to examine life circumstances of development athletes who have sustained a major injury during one season.